Green Marketing and Environmental Protection - Azhagaiah, R.; Ilangovan, A. (Indian Journal of Marketing, 2006)
Environment issue has a significant impact on modern society. The environmental problems arise partly due to marketing and consumption culture, characterized by a ’buy-use-dispose cycle’ for goods and services, which has evolved into the most powerful forces affecting both individual and environment. This led the firms to develop a new or alternative ways of satisfying these unlimited wants. It resulted into environmental problems. Keeping the environment good and clean is a must for not only the good health of the people but also for the continuous supply of goods and services to the people. The mankind has limited resources on the earth with which market must attempt to provide for the world’s unlimited wants. Therefore, there is a need for environmental awareness, environmental protection and environmental perspectives. Hence, in this study an attempt has been made to trace and analyse the concept and role of environmental protection, environmental marketing and green marketing.